The Integration of Social Determinants of Health into Health Information Management Systems and Technologies - Gransberry, Christopher (British Journal of Healthcare and Medical Research, 2023)
The social determinants of health (SDOH) have garnered more and more attention from the public healthcare sector over the past two decades. Aside from medical care, these are the aspects of health that social practices may affect and significantly influence. Several recent significant initiatives have requested enhanced attempts to use health information management (HIM) technology and systems to incorporate SDOH into healthcare centers. However, the data to support the practical use of these guidelines is sparse. The integration of SDOH areas into electronic health records (EHRs) is addressed in this comprehensive literature review, which identifies and evaluates the existing studies. It will also discuss several policy reforms as recommendations to eliminate current technology gaps in healthcare. These reforms include digital programs and technologies, mobile health plans, digital literacy, internet access, and risk prediction assessment.